Genes Required for Mitotic Spindle Assembly in Drosophila S2 Cells - Goshima, Gohta (2007)
The formation of a metaphase spindle, a bipolar microtubule array with centrally aligned chromosomes, is a prerequisite for the faithful segregation of a cell’s genetic material. Using a full-genome RNA interference screen of Drosophila S2 cells, we identified about 200 genes that contribute to spindle assembly, more than half of which were unexpected. The screen, in combination with a variety of secondary assays, led to new insights into how spindle microtubules are generated; how centrosomes are positioned; and how centrioles, centrosomes, and kinetochores are assembled.